Pendidikan Politik pada Masyarakat Jawa di Desa Perkebunan Pernantian - Dipo Piswatama; Windawati Pinem (Journal on Education, 2024)
Political education is a scientific study that discusses the political system, constitution, human rights, general elections, political parties, public policy and political participation. Political education refers to how people in remote villages receive attention from the government to provide an understanding of political education. This research focuses on political education in Javanese society in the Pernantian plantation village. This type of research is qualitative. The qualitative research method focuses on interviewing other people outside the environment and is complex. (Moleong, 1999; Creswell, 2002, Lindloft, 1995), states that qualitative research methods are more inductive. This means that the research step that must be prioritized is data based on facts, symptoms, phenomena, reality which is the theme, then processed, processed, so that at the end of the research it can become a proposition, model or even theory. It is hoped that this research will provide awareness of government performance, because remote villages still lack knowledge about political education. The results of the author's findings from fieldwork reveal that, in the plantation villages, the majority of Javanese people spend their time working and do not care about political education and in fact they are very anti-political education.